On the presence of Dipturus nidarosiensis (Storm, 1881) in the Central Mediterranean area - Carbonara, Pierluigi; Cannas, Rita; Donnaloia, Marilena; Melis, Riccardo; Porcu, Cristina; Spedicato, Maria Teresa; Zupa, Walter; Follesa, Maria Cristina (PeerJ, 2019)
The Norwegian skate Dipturus nidarosiensis (Storm, 1881) has only recently been recorded in the western Mediterranean Sea along the coast of southern Sardinia, off Algeria and the Alboran Sea. The present study confirmed the presence of the species in the Central Mediterranean Sea by identifying morphometric, morphological features and molecular markers. Biological sampling was conducted from 2010 to 2016 on eight specimens collected through commercial landings, offshore observer programmes and scientific surveys in Adriatic and Ionian waters at depths between 320 and 720 m. The total lengths of the specimens (juveniles and adults) ranged from 268 to 1,422 mm, and their body weights ranged from 44.5 to 12,540.0 g. They showed morphometric features that corresponded to those of Norwegian skates in the Northeast Atlantic and the Western Mediterranean. In previous analyses, molecular data were obtained by mitochondrial COI sequences. The haplotype network showed the occurrence of a common haplotype (Hap_1) shared by the individuals from areas in the North Atlantic, Sardinian, Algerian and Spanish Mediterranean Sea areas but not South Africa. The occurrence of individuals in different stages of life (i.e., juveniles, sub-adults and adults) and sexual development (immature and mature) suggested the presence of a species with a permanent reproductive allocation in the deep waters of the Mediterranean, which was exposed to a low level of fishing exploitation. Indeed, the deep depth distribution of the species could be the reason for the absence of information about this species in onshore or offshore fishery data collection programmes and scientific surveys.